Yeast autonomously replicating sequence (ARS): Identification, function, and modification. Issue 7 (6th May 2021) - Tan, Xiao‐Yu; Wu, Xiao‐Le; Han, Ming‐Zhe; Wang, Li; Xu, Li; Li, Bing‐Zhi; Yuan, Ying‐Jin
Abstract: Eukaryotic DNA replication begins with multiple origins of replication (ORIs) and thus exploring and identifying ORIs is essential for further understanding of the DNA replication process. In budding yeast, certain autonomously replicating sequences (ARSs) initiate the replication as ORIs, maintaining the stability of chromosomes and plasmids during genome replication. Currently, ARS identification was further facilitated by the DNA microarray technology and bioinformatics, which is based on the previous experimental methods. The structural and functional properties of ARSs on yeast chromosomes are gradually explored in this field. In addition to the function of initiating replication, there is a growing interest for researchers in the effects of ARSs on gene silencing and expression of genes, particularly the relationship between ARSs and chromosome structure. In this review, we summarized the identification methods of ARSs, especially for the bioinformatics prediction methods over the past few years. The functions of ARSs are discussed in this research, moreover, ARS modification that combined with the high‐throughput sequencing was elaborated as well, shedding further light on the understanding of the roles of ARSs, and providing deep insights towards the optimization of ARSs.